Combining New Awareness and Public Support for Archaeology with In Situ Preservation of an Archaeological Monument. (2nd July 2016) - Van Os, Bertil J.H.; de Groot, Tessa; Schreurs, José; Stappers, Marc; Verschuur, Marjolein
Abstract : Preserving archaeological remains in situ is one of the main objectives of the Valletta Treaty, which was signed by the Dutch government in 1992. Subsequently, preservation in situ has become one of the pillars of archaeological heritage management in the Netherlands. Another objective of the Treaty is the promotion of heritage education and raising of public awareness for the protection and investigation of archaeological heritage. Until recently, this goal has received too little attention. The design and building of an underground visitor centre, DOMunder, raised an important question: How can we transform an archaeological monument into an asset for the community and at the same time ensure long-lasting preservation? Not many parallels exist, as most archaeological sites in urban environments are seen as a burden for development. Sites are generally either excavated or left in situ ; in both cases the archaeology remains invisible and inaccessible to the public. In the case of DOMunder, the location in a wet sedimentary environment provided even more challenges. This paper focuses on a few of the many questions and problems that were raised before and during the building process and the (preliminary) answers and solutions.